Is believing for a normative reason a composite condition? - Cunningham, J (Springer Netherlands, 2017)
Here is a surprisingly neglected question in contemporary epistemology: what is it for an agent to believe that p in response to a normative reason for them to believe that p? On one style of answer, believing for the normative reason that q factors into believing that p in the light of the apparent reason that q, where one can be in that kind of state even if q is false, in conjunction with further independent conditions such as q’s being a normative reason to believe that p. The primary objective of this paper is to demonstrate that that style of answer cannot be right, because we must conceive of believing for a normative reason as constitutively involving a kind of rationality-involving relation that can be instantiated at all only if there is a known fact on the scene, which the agent treats as a normative reason. A secondary objective, achieved along the way, is to demonstrate that in their Prime Time (for the Basing Relation) Errol Lord and Kurt Sylvan do not succeed in undermining the factoring picture in general, only a simple-minded version of it.